AF’AL AL-KALAM AL-INJAZIYYAT FI NASH AL-MASRAHIYYAT AL-BAB LI GHASSAN KANAFANY: DIRASAT TADAWULIYYAT - Muhammad Izzuddin; Abdul Muntaqim Al Anshory (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to: 1) describe the form of illocutionary speech acts in drama script of Ghassan Kanfany's “Al-Baab” based on Searle's perspective; and 2) describe the function of illocutionary speech acts in drama script of Ghassan Kanfany's “Al-Baab” based on Searle's perspective. This research is a descriptive qualitative and field research. The primary data source is drama script of Al-Baab by Ghassan Kanafany and book of Searle Expression and Meaning: Study in The Theory of Speech Acts. Secondary data are articles and books of pragmatics. The data collection technique uses reading techniques and note-taking techniques. The data analysis technique uses data reduction, data display, and drawing conclusions. The results of this study are: 1) illocutionary speech acts in Ghassan Kanafany's drama script Al-baab based on Searle's perspective there are 5 forms (in 45 data), namely assertive speech acts (24 data), directive speech acts (10 data), commissive speech acts (4 data), expressive speech acts (5 data), declarative speech acts (2 data); and 2) illocutionary speech acts in Ghassan Kanafany's play Al-baab based on Searle's perspective there are 14 functions (in 45 data), namely argues (3 data), informs (12 data), explains (5 data), convinces (2 data), states (2 data), commands (6 data), prohibits (2 data), ask (2 data), refuse (1 data), promise (3 data), disappointed (3 data), angry (1 data), hate (1 data), and punish (2 data).